Authorship Improprieties: Analyzing the Practice of Including Advisers as Co-Authors in Students’ Research - Aguilar, Mark Gabriel (Educational Challenges, 2024)
Purpose. This research aims to investigate the prevalent practice of including advisers as co-authors in students’ research works, with a specific focus on understanding the attitudes of the academic community, particularly students and educators. The study seeks to explore. Students’ and educators’ perceptions, beliefs, and/or opinions regarding the practice raise concerns in higher education institutions worldwide. Methodology. Through a descriptive-correlational research design following a quantitative research approach, the researcher gathered data on the attitudes of 200 students and 200 educators of 4 Higher Education Institutions in Region IV-A, Philippines, towards the inclusion of advisers as co-authors in students’ theses, particularly when presented in conferences and published in journals. The collected data is analyzed to identify prevailing opinions and perspectives within the academic community. This analysis takes into account factors such as mentorship, intellectual contribution, and ethical considerations related to authorship attribution. By weighing these factors, the researcher forms a stance on the practice and offers recommendations for its ethical implementation. Results revealed differing opinions between students and educators. Moreover, significant differences in the attitudes of faculty members towards the practice when grouped based on their highest educational attainment, academic rank, and tenure were established, as well as the significant relationship between the research engagement and productivity of faculty members, and their attitude towards the matter. Although the inclusion of advisers in students’ theses was found acceptable within the academic community, the authorship guidelines set by the Committee on Publication Ethics, also known as COPE, suggest otherwise. Conclusion. These findings contribute to the existing literature on academic authorship improprieties and provide insights into the attitudes and opinions of the academic community. They are expected to stimulate discussions, fostering a better understanding of the implications of including advisers as co-authors in students’ research works. The paper also offers practical recommendations to promote transparency, fairness, and integrity in authorship practices, ensuring that credit is appropriately attributed to all contributors in academic publications.